A study on the perception of hand washing and health status in Korean adults. Issue 3 (22nd January 2021) - Park, Soohee
Abstract : Abstract: This study aimed to investigate the perception about hand washing and health status among Koreans using the data from the Community Health Survey. We examined the differences in the perceptions about hand washing and health statuses of 220, 440 participants of the 2017 community health survey. The sample was divided into groups based on demographic variables, perceptions about hand washing, and prevalence of metabolic diseases. Participants' demographic characteristics were analyzed using frequency, and perceptions about hand washing and subjective health status-related parameters were analyzed using t tests. The prevalence of metabolic disorder was analyzed with χ 2 tests. There were significant differences in subjective health status, subjective oral health status, and perceived obesity in the positive and negative hand washing perception groups ( P  < .01). The prevalence rate of hypertension and diabetes mellitus significantly differed in the positive and negative hand washing perception groups ( P  < .01), but no differences were observed for hyperlipidemia ( P  < .01). This study showed that positive hand washing perception is associated with good health care practices. The perceptions of hand washing, which are formed during early childhood, were closely associated with health status. This finding could be useful evidence for developing programs focusing on major health behaviors and levels of health.